Anti-TNF-α therapies for the treatment of Crohn's disease: the past, present and future. (1st February 2016) - Berns, Marc; Hommes, Daniel W.
ABSTRACT: Introduction : Anti-TNF-α therapy is a novel approach that has transformed the way moderate-to-severe Crohn's disease (CD) is treated and has significantly improved clinical outcomes of patients with enhanced remission induction and maintenance efficacies. As a result, anti-TNF-α agents have become the primary cost driver in the treatment of CD, as the frequency of hospitalizations and surgical interventions have been drastically reduced. Areas Covered : In the review, the authors cover current anti-TNF-α treatments for CD including efficacy, mechanisms of action, pharmacokinetics and safety. In addition, the authors discuss future anti-TNF-α agents currently in the development pipeline including biosimilars, golimumab, oral AVX-470, TNF-α-kinoid vaccine, and non-biologic HMPL-004. Expert opinion : While new therapeutics are in the pipeline like anti-integrin and anti-interleukin therapeutics, anti-TNF-α therapy remains at the forefront of CD treatment due to its long-term efficacy and safety profiles. The next horizon for new anti-TNF-α agents is biosimilars, which offer comparable safety and effectiveness to the originator molecules. Biosimilars promise to expand accessibility to anti-TNF-α therapy while significantly reducing the cost burden to patients and healthcare systems.